Use of fitness-related behavioral endpoints to assess the effects of 17α-ethinylestradiol on a brackish water population of common mummichog, Fundulus heteroclitus. Issue 6 (2nd November 2019) - Dzieweczynski, Teresa L.; Greaney, Nicole E.; Farrin, Sydney R.; Ackerman, Erika R.; Forrette, Lindsay M.
Abstract : Endocrine-disrupting chemicals like the estrogen mimic 17α-ethinylestradiol (EE2) are released into aquatic environments from various sources and can have pronounced effects on organisms and the health of the ecosystem. Exposed species experience morphological changes, but there is little research on behavioral alterations, especially in marine organisms. This study focuses on the mummichog, Fundulus heteroclitus, an estuarine species that is a common subject of ecotoxicology research. Mummichog were exposed to different amounts of EE2 (0 ng/L, 10 ng/L, and 100 ng/L) and their behavior was examined in fitness-related assays (Empty Tank, Novel Environment, Shoaling, Foraging) once per week for 4 weeks. Exposure was found to affect behavior, especially in the foraging and shoaling contexts. The higher dose had the greatest effects on behavior, such as increasing the amount of time individuals took to find food in the Foraging assay. Both doses impacted activity levels in the Shoaling assay and eating in the Foraging assay. Females were less bold than males overall, although EE2 exposure was not found to have a significant sex-specific effect on behavior. Exposure altered fitness-related behaviors and thus may generate evolutionary consequences. This study stresses the importance of examining marine species in addition to freshwater species in ecotoxicology studies and reinforces the utility of behavior as a useful and sensitive endpoint. Additionally, it adds to our understanding of behavior within this species in general.